Mr. Frank Harina, Dulce, New Mexico (Raton, New Mexico, 1963)
Typed letter written to Frank Harina from Unknown about Apache land located in the upper Cimarroncito.
Mater List Item # 3
File location is in the New Mexico File Cabinets
Keywords: Harina, Frank; Phillips, Waite; Buffalo Bill; La Juan, Tony; Webster, Sturat; Beaubien, Charles; Miranda; Maximilian; Armijo (Governor); Kearny (General); Maxwell; Carson; Maxwell's Rancho; Fort Quasi; National Boy Scout Organization; Maxwell Land Grant; Apache Land; Ranch; Ownership; Organizations; Cimarroncito, New Mexico; Cimarron, New Mexico; Rayado, New Mexico